PENGARUH MEDIA STICK PUPPETS TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN ANAK USIA 5-6 TAHUN DI TK AL-FAJAR KECAMATAN TAMPAN KOTA PEKANBARU - Syaputri, Hesty Ikhwani; Indarto, Wusono; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this observation is to analyze the effect of stick puppets media toward the ability of numeral concept recognizing of children age 5-6 years. This observation held in TK Al-Fajar Tampan Districts Pekanbaru City during May 2017. The observation was using the experiment method by one group pretest protest design of 21 children in total. The kind of instrument used in this observation was using observation sheet to record the activity during it. Data analysis technique used t-test with SPSS 20.0. Research hypothesis is the activity of the use of stick puppets media has an effect to toward the ability of numeral concept recognizing of children age 5-6 years in TK Al-Fajar Tampan Districts Pekanbaru City. This can be known from the analysis of data obtained thitung = 24,216 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a difference in the ability of numeral concept recognizing of significant of students after the use of stick puppets media in learning. The hypothesis test can be seen thitung= 24,216 > ttabel= 2,086. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiments by applying the use of stick puppets media. The effect of stick puppets media toward the ability of numeral concept recognizing of children age 5-6 years in TK Al-Fajar Tampan Districts Pekanbaru City of 50,20%.Keywords: The ability of numeral concept recognizing, Stick Puppets Media.